PERANAN GENDER DALAM PROSES PEMBUATAN KOPRA DI DESA LOLAH TIGA, KECAMATAN TOMBARIRI TIMUR, KABUPATEN MINAHASA - Biondi F. Tiolung; Martha M. Sendow; Ribka M. Kumaat (Sam Ratulangi University, 2017)
This study aims to determine the role of gender in the process of making copra in Lolah Tiga Village, Tombariri Timur District. The study was conducted from May to June 2017. The data used were primary and secondary data. Primary data through interviews using questionnaires to 30 respondents and secondary data obtained from Village Office of Lolah Tiga. This analysis uses descriptive analysis. The research results show that gender role in the process of making the most copra in male labor in the activities of picking, transporting, stripping and selling. While done by female workers. The activity of stripping and separating meat is done by male and female laborers.